Wisdom and Islamic Thoughts in the Lyrics of Siti Nurhaliza’s Hari Raya Songs - Laengkang, Abd Ganing (Andalas International Journal of Socio-Humanities, 2024)
This study looks at the wisdom of song lyricists during the celebration of hari raya, as depicted through Islamic values and thoughts. The research question revolves around the extent to which song lyricists produce works that embody Islamic values and thoughts in celebrating the triumphs of the Islamic community. The objective of this study is to identify the Islamic values and thoughts within ten raya songs sung by Siti Nurhaliza. The researchers utilised the conceptual framework of local wisdom that aligns with the goals and functions of Islamic artistic works. The aim of Islamic art is to bring Muslims closer to Allah, imparting values of monotheism, faith, morality, and camaraderie, advocating goodness and preventing evil. Therefore, any song lyrics embodying the values of monotheism, devotion, faith, ethics, or any elements promoting goodness and well-being are categorised as Islamic values and thoughts. The findings indicate that the lyrics of the raya songs not only entertain but also encompass ten Islamic values and thoughts. Among the values and Islamic thoughts are monotheism, gratitude, remembrance, soul purification, sincerity, and so on. The raya song lyrics can guide individuals towards salvation in this world and the hereafter.